Standardising public service: the experiences of call-centre workers in the Canadian federal government. (1st July 2009) - Norene Pupo,; Andrea Noack,
Abstract : This paper explores the impact of the adoption of neoliberal economic policies and practices on public sector jobs within the Canadian Federal government. In recent years, employment in the public sector has been increasingly shifted to a call-centre format, thereby transforming the working conditions of public servants as well as access to services enjoyed by Canadians. By adopting work practices, technologies and managerial techniques usually found within the private sector, we argue that the call-centre format fundamentally transforms the notion of public 'service' from secure employment and a dynamic career to that of a routine, Taylorised job. In this process, standardised interactions redefine the notion of public service and the role of the public servant.